A molecular investigation into the genetic networks that respond to the mechanical characteristics of the microgravity environment experienced by A. thaliana during spaceflight. - Henning, Jarret Evans (Proceedings of the Wisconsin Space Conference, 2019)
Plants respond to stresses related to microgravity. Calcium (Ca2+) and Reactive Oxygen Species (ROS) have been shown to be involved in the signaling of rapid systemic response (figures 2 and 3; Gilroy et al., 2016 and Steinhorst et al., 2013). RNAseq has been used to identify genes affected by point mutations within the touch responsive gene CML24 (TCH2 in figure 1) identifying genes that are involved in the tch2 signaling pathway. By using bioinformatics, network analysis has been performed (figure 1) to help determine the role that the gene CP1 (AT5G49480.1) plays in touch response and calcium signaling. New phenotyping protocols have been developed to analyze the effect of mechanical stimulation through vibrations producing a standardized way in which the effects of vibrations on plants are measured and tested to determine whether the effects can be mitigated or enhanced through mutations. This work is funded by NASA and WSGC.